PENANAMAN NILAI PEDULI LINGKUNGAN DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM - Yeni Lestari (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
Abstract: This  study  aims  to  describe  the  cultivation  of  environmental  caring  values  in science  learning  in  high  school  students  of  N  Bhayangkara  Elementary  School  year 2016/2017  and  describes  the  supporting  factors  and  their  inhibitors.  This  research  is  a qualitative descriptive research. Techniques of collecting data using interviews, observation, and  documentation.  Data  analysis  uses  data  collection,  data  reduction,  data  presentation, and conclusions. Validity checks data using source triangulation, technique, and time. The results showed that teachers in planning science learning include habituation, exemplary and learning  while  doing.  The  steps  taken  by  the  teacher  include:  using  learning  media  and environment  as  a  place  of  learning.  Teachers  in  conducting  assessments  focus  more  on affective  judgments.  Supporting  factors:  the  performance  of  teachers,  principals  and gardeners  in  guiding  students  and  the  existence  of  learning  media  that  allows  students  to understand  the  value  of  environmental  care.  Inhibiting  factors:  lack  of  learning  time  of science and family role in instilling environmental caring value.